Quantitative Estimation of Carbon Stock Reserve in Angsana (Pterocarpus indicus): Study of Unesa Lidah Wetan Campus Forest - Betty Andriani; Rachmadiarti, Fida; Kuntjoro, Sunu (LenteraBio : Berkala Ilmiah Biologi, 2025)
Angsana (Pterocarpus indicus) is a plant with a high carbon sequestration rate, which dominates in the Unesa Lidah Wetan Campus Forest. Carbon sequestration by plants can minimize microclimate changes caused by increasing greenhouse gases (GHGs). This research needs to be done because the calculation of carbon stocks in angsana in the research location has not been recorded. The purpose of this study was to describe the biomass, leaf chlorophyll content, and leaf surface area of angsana, evaluate carbon stocks in angsana, and analyze the relationship between biomass, leaf chlorophyll content, and leaf surface area of angsana with the amount of carbon stock stored by angsana in Unesa Campus Forest Lidah Wetan. This research used non-destructive carbon stock estimation methods, and the Kettering allometric equation. Based on the research conducted, it was found that angsana in the Unesa Lidah Wetan campus forest had an average biomass of 213.47 Kg, an average chlorophyll content of 22.52 mg/L, and an average leaf surface area of 38.83 cm2, with carbon storage of 100.33 Kg C / tree. There is a positive correlation between biomass of angsana, chlorophyll content of angsana leaves, and leaf surface area of angsana with carbon stock, namely the greater the biomass, chlorophyll content, and leaf surface area of angsana, the higher the carbon stock stored in angsana.